Value of the lung immune prognostic index in patients with advanced small cell lung cancer treated with programmed death-ligand 1 and programmed death-1 inhibitors in the Chinese alpine region - Zhang, Meiling; Hao, Jingwei; Wu, Yunjiao; Gao, Ziyi; Wang, Meng (Frontiers in Oncology, 2024)
Purpose: To assess the potential added value of the lung immune prognostic index (LIPI) in patients with small cell lung cancer (SCLC), treated with programmed death-ligand 1 (PD-L1)/ programmed death-1 (PD-1) inhibitors, who lived in the Chinese alpine region. Methods: 120 SCLC patients treated with PD-L1/PD-1 inhibitors were divided into three LIPI groups, from July 2018 to April 2021. Cox regression models were used to evaluate the prognostic effect of three LIPI groups on overall survival (OS) and progression-free survival (PFS). Logistic regression analysis was conducted to explore the association between immune-related adverse events (irAEs) and the pretreatment of neutrophil-to-lymphocyte ratio (dNLR), lactate dehydrogenase (LDH), and LIPI. Results: The median OS was 4.5, 6.3, and 10.0 months (p=0.001) and the median PFS was 2.5, 4.3, and 5.3 months (p=0.049) for Poor, Intermediate, and Good LIPI, respectively. The disease control rate (DCR) was also higher in the Good LIPI group (p=0.003). Moreover, multivariate analysis confirmed that worse LIPI was correlated with shorter OS and PFS. dNLR was associated with the onset of irAEs, not LIPI. Conclusion: The LIPI might be a promising predictive and prognostic biomarker in SCLC patients treated with PD-L1/PD-1 inhibitors in the Chinese Alpine region.